(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In recent years, special attention has been paid to the issues of protecting pasture lands in our country, ensuring their effective use and combating degradation. This article presents measures for the use and conservation of pastureland, as well as proposals.